Heat transfer - Dr. Khaled BELHOUCHET (University of M'sila, 2024)
This document serves as a pedagogical support for the course Heat Transfer, designed for second-year students in Renewable Energy. The aim of this course is to provide students with a comprehensive understanding of the mechanisms, principles, and applications of heat transfer in various energy systems. As heat transfer plays a fundamental role in renewable energy technologies—such as solar thermal systems, geothermal energy, biomass conversion, and energy storage—mastering its theoretical and practical aspects is essential for future engineers and researchers in this field. The course introduces students to the three fundamental modes of heat transfer: conduction, convection, and radiation. Through this teaching aid, learners will be guided to: 1. Derive and interpret the governing equations that describe the behavior of heat transfer in different physical situations, ensuring a strong theoretical foundation. 2. Develop analytical and numerical solutions for problems involving heat conduction and convection, emphasizing both mathematical rigor and practical engineering relevance. 3. Analyze and solve radiative heat transfer problems using analytical approaches, allowing students to understand thermal interactions between surfaces and within enclosures. In addition to theoretical content, this document includes examples, exercises, and problem-solving strategies aimed at reinforcing conceptual understanding and enhancing problem-solving skills. It is intended to serve both as a reference material during lectures and as a self-study resource, helping students connect fundamental heat transfer concepts to renewable energy applications and real-world systems.
Keywords: Heat transfer; Renewable energy; Conduction; Convection; Radiation; Solar thermal; Geothermal; Biomass; Energy storage; Thermal analysis.